Pengaruh Keputusan Investasi Dan Keputusan Pendanaan Terhadap Nilai Perusahaan - Siti Wardani Bakri Katti (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2020)
This research is aimed to know the influence of invesment decision and funding decision partially and simultaneously toward company value at property and real estate companies listed in the Indonesia Stock Exchange from 2014 to 2017. The sample uses the method of purposive sampling. The populations of this research are all companies of property and real estate. The population of 48 companies obtained by 27 companies is as research sample. The analysis data uses the multiple linier regression analysis. Based on the analysis data can be concluded that the investment decision influences significantly toward the company value. The funding decision influences significantly toward the company value. The test result of model suitability shows the investment decision and funding decision influence significantly toward the company value. The value of determination of coefficient (R2) about 0.511 shows that the influence of investment decision and funding decision toward company value about 51,1%, and the remains are 48,9% are influenced by other variability outside of the research. Keywords—: Investment Decision; Funding Decision; Company Value; Property and Real Estate.